Hubungan Tingkat Pendidikan Dan Pengetahuan Dengan Persepsi Konsumen Tentang Kualitas Dan Manfaat Beras Organik Di Kota Surakarta - Istiqomah, Agustin, Dr. Mutalazimah, SKM, M.Kes, Rusdin Rauf, STP., MP (2016)
Education affects consumers toward organic rice elections. Knowledge also has an important role in assessing and determining a perception. Perception is the process of observation on an object through the sensing to be interpreted on the environment. Knowledge is the result of human sensing that not only know but also can perform an assessment of a particular object. Quantitative research with cross-sectional approach was conducted. The number of respondents, as much as 44 people, were obtained by consecutive random sampling technique. The educational level data obtained through interviews, while consumer perceptions questionnaire data with the number of 21 statements and questionnaires knowledge as much as 20 statements. Pearson product moment and Spearman rank were used in statistical test. Consumers with higher education level indicated than a perception about the quality and benefits of organic rice higher than primary and secondary education levels were 18,3% respectivaly. The good perception on quality and benefit of organic rice displayed by consumers with less knowledge category, was 33,3%. There was a relationship between level of education and consumer perception on the quality and benefits of organic rice in Surakarta (p = 0.030). There was a relationship between knowledge and perceptions of consumers about the quality and benefits of organic rice in Surakarta (p = 0.010).